Awareness and Attitude towards modern technological approaches to enrich classroom teaching-learning process.-A study Undertaken on M.Ed. students in the Academic year of 2005/2006 at the University of Jaffna - Nithlavarnan, A.; Kalamany, T. (My University, 2008)
The attitudes that characterize teachers and learners in learners in relation to the modern technological approaches in education have been identified as an important factor that affect teachers’ and learners’ motivation, interests and performance in technology enriched teaching-learning environments. Meanwhile, their awareness of the modern technological approaches in education may shape their attitudes and behaviors. This study was conducted to investigate the M.Ed. students in University of Jaffna. Specifically the study assessed1.)Various types of quality inputs and teaching strategies used by participants in their teaching, 2.)Barriers/constrains faced by teachers in their classroom teaching related technology integration, 3.) Participants’ attitudes towards expected performance from teachers regarding modern educational technology. This study is both qualitative and quantitative in design, using questionnaire as a main tool for collecting data. Qualitative data were collected through open ended questions in the questionnaire and informal discussion with participants. Seventy seven M.Ed. students at Jaffna center participated in this study. The results of the study revealed that the M.Ed. students, who participated had positive perceptions regarding the use of modern technological approaches in education. The study also indicated that the students had positive attitudes. More over most of the participants agreed, particular performances expected from teachers regarding modern educational technology usage. Lastly, this study serves as a starting-point for research that more broadly explores teachers’ and learners’ perceptions and attitudes of the modern technological approaches in Education.